Pendekatan Pragmatik Novel Asriaci “Melodylan” - Bangun, Chelsy; Anggereni, Theresia; Naibaho, Jessica; Yuhdi, Achmad (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The purpose of this research is to analyze parts of the novel "Melodylan". The analysis of this novel uses a pragmatic approach, trying to appreciate literary works based on their function to provide and convey certain goals to the reader. The aim of this research is to describe the novel Melodylan by Asriaci using a pragmatic approach. This research method is qualitative descriptive research. This research is descriptive literature research. Data collection techniques are only carried out using reading and note-taking techniques. Meanwhile, the results of this research are that readers can gain values ​​about the story of romance and friendship in high school which depicts the characters in the novel Melodylan. Apart from that, readers can also learn lessons about when we should give in and lower our ego to avoid problems. Analysis This novel uses a pragmatic approach, trying to appreciate literary works based on their function to provide and convey certain goals to readers.